Monitoring Lereng Menggunakan Prisma Untuk Mengetahui Pergerakan Pada Lereng Inpit dan Ekspit PT Sago Prima Pratama (J Resources) Site Seruyung Kecamatan Sebuku, Kabupaten Nunukan,Kalimantan Utara - Aiv Fajri Muchtar; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT Sago Prima Pratama is a company engaged in the field of gold mining with an open mining system. Calculation and analysis of slope stability is very important to do, especially in open pit mining using the open pit method. Rock masses that were initially stable and undisturbed were dug up (disturbed) so that they could lose stability and cause landslides. If landslides occur, there will be hazards that disrupt the mining process so that production will be disrupted. From the calculation using Surpac software it is known that the pit depth is 150 meters from the ground surface. Movement often occurs on the slope, therefore slopes must be monitored so that movement on the slope can be known and can be known hazards on vulnerable slopes. Monitoring is usually done by looking at prism data. From these data we can see how much the slope is moving. With this monitoring can anticipate the potential for landslides early, so that treatment can be done earlier. Monitoring carried out at inpit has a range that ranges av. displacement at the study site during the August 14-29 2018 is 0.023mm to 0.177mm and the range av. instant velocity ranges from 0.30 - 1.33 mm / hour The fastest movement is at the BLS and the lowest is at the MSC.Keywords: Monitoring, slope, stable, displacement, velocity